THE INFLUENCE OF CALCIUM ANTAGONISTS AND Β-BLOCKERS ON PLATELET FUNCTION AND RHEOLOGICAL BLOOD CHARACTERISTICS IN PATIENTS WITH ISCHEMIC BLOOD DISEASE - G. A. Chervjakova; V. N. Soboleva (Российский кардиологический журнал, 2003)
The influence of calcium antagonists and β-blockers on platelet function and rheological blood characteristics in patients with ischemic blood disease.